Sistem Pendukung Keputusan e-voting Seleksi Pemimpin menggunakan Metode Analytical Hierarchy Process - Arianti Ika Prastiwi; Winny Purbaratri; Muhammad Fachrur Razi (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2023)
Elections for the leaders of the Student Executive Board are held every year. e-voting is one of the most important components and forms of democracy. The result of voting is always dissatisfaction from voters. To become a candidate for the Head of BEM, a selection process is required. When choosing a Student Executive Board Leader, there are several criteria that must be met by prospective candidates. The issue of selecting leaders was also discussed by Andi Rosano in choosing the Village Head. The difficulty for voters is to get a leader candidate who has advantages in different fields. Because of that, a decision support system is needed to assist voters in determining the leader of the Student Executive Board. The Decision Support System using the Analytical Hierachy Process Method can assist voters in selecting candidates for the Student Executive Board leaders. Methodology This research was carried out using a 2 (two) method approach, namely a field study conducted by means of interviews with the student affairs section that takes care of the election of the Student Executive Board Leader and literature study to collect information related to decision support systems using the Analytical Hierarchy Process method. The results of the research are in the form of a Decision Support System application using the AHP Method to assist the committee in getting the right results